Dinamika Pengembangan Kurikulum Pendidikan Agama Islam dalam Konteks Kurikulum Merdeka: Kajian Literatur - Muahmmad Fajar; Mike Andrini; Chairul Anwar; Syaiful Anwar; Muhammmad Idris (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the dynamics of Islamic Religious Education (PAI) curriculum development in the context of the Merdeka Curriculum, as well as to identify implementation challenges and formulate a synthesis of relevant solutions. This research employs a qualitative approach using a literature review method. Data were collected from scientific journal articles, books, and educational policy documents, and analyzed using content analysis through data reduction, data display, and conclusion drawing. The findings indicate that the PAI curriculum has transformed from a traditional approach into a competency-based, contextual, and character-oriented curriculum. However, its implementation still faces several challenges, including limited teacher competence, infrastructure disparities, and the suboptimal integration of Islamic values with modern learning approaches. These conditions create a gap between the ideal curriculum design and its practical implementation. Based on the synthesis of findings, this study proposes an integrative model for PAI curriculum development consisting of three main pillars: teacher competency transformation, value-based technology integration, and contextual learning enhancement. These pillars are interconnected and essential for creating adaptive, relevant, and value-oriented PAI learning. This study contributes by offering an analytical perspective that integrates curriculum development, implementation challenges, and learning solutions into a comprehensive framework.